The value of the 12-lead electrocardiogram in the prediction of sudden cardiac death. (26th April 2023) - Calò, Leonardo; Lanza, Oreste; Crescenzi, Cinzia; Parisi, Cristian; Panattoni, Germana; Martino, Annamaria; Rebecchi, Marco; Tarzia, Pierpaolo; Ciampi, Pellegrino; Romeo, Fabiana; Canestrelli, Stefano; Silvetti, Elisa; et al.
Abstract: Sudden cardiac death (SCD) can be caused by several clinical conditions, overt or misconceived, which recognize different pathophysiologies determining the development of fatal arrhythmic events. In the various forms of structural heart disease such as ischaemic heart disease, cardiomyopathies (e.g. hypertrophic cardiomyopathy, dilated cardiomyopathy, and arrhythmogenic cardiomyopathy), channelopathies (e.g. long-QT syndrome, congenital short QT, Brugada syndrome, early repolarization (ER) syndrome, and idiopathic ventricular fibrillation) but also in the apparently healthy subject, the 12-lead electrocardiogram (ECG) has proved, over the years, to be a reliable and readily available method for stratifying the risk of adverse arrhythmic events and consequently SCD. Several electrocardiographic markers have been shown to be associated with adverse outcomes in different types of patients. Although with different sensitivity and specificity in each clinical condition, depolarization abnormalities, such as QRS fragmentation, Q waves, QRS duration, left posterior fascicular block, low QRS voltage, and left ventricular hypertrophy and similarly repolarization abnormalities as ER pattern, T wave alternans, QT interval, and QT dispersion, have shown significant efficacy in predicting SCD. Despite the advancement of techniques especially in the field of imaging, the correct interpretation of the 12-lead ECG remains, therefore, an effective tool for assessing the possible prognostic outcome in terms of arrhythmic risk and SCD in different types of patients.